Utility of fetal cardiovascular magnetic resonance imaging in assessing the fetuses with complete vascular ring - Zhang, Xia; Zhu, Ming; Dong, Su-Zhen (Frontiers in Pediatrics, 2023)
Objective This study aimed to report our experience in qualitative and quantitative evaluation of fetal complete vascular ring (CVR) using fetal cardiovascular magnetic resonance imaging (MRI) to improve prenatal diagnosis and make early postnatal management possible. Methods A retrospective case-control study was performed on cases of CVR diagnosed using fetal cardiovascular MRI, and confirmed by postnatal imaging diagnosis. Associated abnormalities were recorded. The diameters of aortic arch isthmus (AoI) and ductus arteriosus (DA), and tracheal diameters in fetuses with tracheal compression were measured and compared with those of the control group. Results All fetal CVR cases in this study included right aortic arch (RAA) with aberrant left subclavian artery (ALSA) and left DA (n = 93), double aortic arch (DAA) (n = 29), RAA with mirror-image branching and retroesophageal left ductus arteriosus (RLDA) (n = 8). Compared with the control group, the diameters of AoI in fetuses with DAA were decreased (p < 0.001), and the diameters of DA in fetuses with RAA with ALSA and left DA were increased (p < 0.001). The diameters of AoI and DA were positively correlated with gestational age (GA) in the normal control group (both p < 0.001); The diameters of AoI and DA were also positively correlated with GA in RAA with ALSA and left DA subgroup (both p < 0.001) and RAA with mirror-image branching and RLDA subgroup (AoI: p = 0.003; DA: p = 0.002); The diameters of DA were positively associated with GA in DAA subgroup (p < 0.001), however, there was no linear tendency between the diameters of AoI and GA in the DAA subgroup (p = 0.074). There were CVR fetuses with associated intracardiac malformation (n = 13), especially ventricular septal defect rather than complex heart disease, and extracardiac malformation (n = 14). Sixteen fetuses were shown the airway compression whose tracheal diameters were smaller than the normal (p < 0.001). Conclusions The altered diameters of AoI and DA can be detected and measured in CVR fetuses using fetal cardiovascular MRI. Fetal CVR can occur alone or with intracardiac and extracardiac malformation. Fetal CVR can be associated with prenatal airway compression.